PERAN PEREMPUAN DALAM PEMBERDAYAAN EKONOMI SYARIAH - Huda, Alamul (Fakultas Syariah, 2013)
Women movement in contemporary context is a ovement which has value, meaning and its own’s potential. The movement covers several factors in society, and one of them is women’s effort and strenght in improving living standart of the society. Furthermore, actualization of this empowerment is in forms of building and developing women cooperative institution as a medium for increaing economics’ welfare of socety. The succes of that cooperative institution gives proof and important meaning of the influence and the present of women in the middle of society as well as deconsts doubt stigma towards women’s role and their strenght. Then, phenomenollogy, the existence of women cooperative institution is the actualization of role and economics empowerment of society by women is the proof of women’s strenght in social realm and society. Gerakan perempuan dalam konteks kekinian adalah gerakan yang memiliki nilai, arti dan potensi tersendiri. Hal ini meliputi sekian banyak factor di dalam masyarakat, dan salah satu diantaranya adalah daya ikhtiyar dan upaya kekuatan perempuan dalam meningkatkan taraf hidup masyarakat. Selanjutnya, aktualisasi pemberdayaan ini adalah dalam bentuk pendirian dan pengembangan koperasi wanita sebagai sarana meningkatkan kesejahteraan ekonomi masyarakat. Kesuksesan yang ditunjukkan oleh koperasi wanita ini memberi bukti dan arti penting, makna pengaruh dan kehadiran perempuan di tengah masyarakat, sekaligus mendobrak stigma keraguan akan peran dan kekuatan perempuan. Selanjutnya, secara fenomenologis, eksistensi koperasi wanita adalah aktualisasi peran dan pemberdayaan ekonomi masyarakat oleh perempuan merupakan bukti akan kekuatan perempuan dalam ranah social dan masyarakat.